Kinematic variability of late Cenozoic fault systems and contrasting mountain building processes in the Alxa block, western China. (January 2021) - Zhang, Jin; Cunningham, Dickson; Yun, Long; Qu, Junfeng; Zhao, Heng; Zhang, Beihang; Niu, Pengfei; Hui, Jie
Graphical abstract: Highlights: Late Cenozoic fault systems partly bound and transect the Alxa Block north of Tibet. Fault orientations and kinematics suggest inherited structures are reactivated. Sinistral transpressional faults converge westwards towards the Altyn Tagh Fault. The regional fault network produces diverse orogen types and bulk eastward extrusion. Crustal thinning in the Ejina Basin may be a response to Alxa Block extrusion. Abstract: In this study, new structural field data and geological observations are coupled with remote sensing analysis and compilation of previous published work to establish a new kinematic framework for the neotectonic reactivation of the Alxa block, China. The Alxa block occupies a key position in Central Asia north and east of the contractional and sinistrally transpressive deforming zones of the Qilianshan-Hexi Corridor-easternmost Altyn Tagh Fault and Beishan deforming belts, south of the sinistrally transpressive southernmost Gobi Altai, and west of – or overlapping with - Ordos block extensional and transtensional graben systems. In addition, the Alxa block is internally transected by important fault systems (Bayan Nuru, Bayanwula, Chahanbulage) that record previously unrecognized Late Cenozoic activity. Active mountain building processes in the Alxa block show remarkable variation from large extensional horst blocks (Helanshan, SW Langshan, SW Yabrai) to localized uplifts along sinistral wrench-belts (Bigesitai) to dominantly contractional (Longshoushan) and sinistral transpressional ranges (Helishan). The triangular wedge-shape of the Alxa block likely pre-disposed it to eastward extrusion in response to NE-directed India-Eurasia collision-derived compressional stresses from the south, and E-W tensional forces driven by Pacific margin rollback to the east. A combination of inherited regional lithospheric structure and the modern east-directed geodetically derived crustal velocity field led to: 1) crustal thinning and subsidence of the Ejina basin to the west in the wake of the eastward extruding Alxa block, and 2) distributed sinistral transtension and crustal extension within the Alxa block interior, and in the Hetao and Yinchuan grabens to the east.